(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
In this paper, systematic experimental investigations were carried out for a wickless heat pipe with flat evaporator having dimensions (100x100x30) mm. Flat-square electrical element was used to simulate the heat source of electronic part with dimensions of (100x100) mm. The aim of this paper presents the effect of fill ratio and cooling water mass flow rate on thermal performance of a wickless heat pipe. Experiments were performed to evaluate performance of wickless heat pipe for range of input power from 10 W to 100 W. The fill ratios used in the present work were 15%, 25%50% and 85%. The cooling water mass flow rate was also changed from 0.0083 kg/s to 0.033 kg/s. Experimental results showed that the maximum value of wall evaporator temperature was 115°C at input power of 100 W and a fill ratio of 15%. Results also showed that the maximum value of the total resistance was 0.8°C/W.